Biotechnology and medical science proceedings of the 2016 International Conference on Biotechnology and Medical Science - International Conference on Biotechnology and Medical Science (2016 : Nanjing, China); Yong, Zhang (Singapore : World Scientific Publishing Company, 2017)
'This book is an all-embracing review of biotechnology, biomedical engineering, bioinformatics, pharmacy and medicinal chemistry, and biopharmaceutical technology. Existing theories and the latest findings are discussed. Researchers, engineers, academics, and industry professionals will find this book an invaluable read.'--Publisher's website.
Title from PDF file title page (viewed September 29, 2016).
Includes bibliographical references.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Medicine -- congresses; Biotechnology -- Congresses; Electronic books